RGD-based Therapy: Principles of Selectivity - A. Rubtsov, Mikhail; S. Syrkina, Marina; Aliev, Gjumrakch (Current Pharmaceutical Design, 2016)
Design of selective anticancer drugs that are targeting RGD-binding integrin receptors which are known to be one of the perspective directions in the field of oncology. Significant progress in the development and application of these types compounds is already demonstrated. The accumulating body of basic and clinical evidence demonstrates potential significant effects on both in vitro and in vivo experimental models. However, the specific mechanism of action of these compounds is generally not a fully elucidated or the exact target responsible for the achievement of stated effects hasn't yet been defined sufficiently. To date eight types of integrin receptors, which are capable to recognize RGD-motif in natural ligands, has in fact been identified as (namely αIIbβ3, αvβ1, αvβ3, αvβ5, αvβ6, αvβ8, α5β1, α8β1). Even so, the estimation of the affinity of one particular RGD-bearing anticancer agent is often based on the determination of the binding efficacy to only one or rarely two integrin receptors. Traditionally the range of targets is restricted by the integrins, which are known to be highly expressed in a particular model system. While potential interactions of such an agent with other RGD-recognizing receptors usually remain beyond the research. Nonetheless, such interactions may also affect the viability and behavior of cancer cells. In this review we attempt to critically analyze the principles of selectivity achievement in the case of RGD-bearing natural ligands and the applicability of these principles in the context of the anticancer drug design.
Keywords: anticancer therapy